A Game-Theoretical Analysis of Anti-Corruption Measures - Kobrč, Marek (2014)
In this thesis, I suggest a new anti-corruption measure. The measure makes corruption unfeasible by making the interests of the culprits incompatible. This is achieved by giving immunity to the culprit who reports the corruption. Said culprit is allowed to retain any benefits he has already obtained and is given a reward for making the report. The purpose of the measure is to discourage the parties from corruption ex ante. The paper presents an argument that no immunization and reward take place, because the culprits are rendered unable to find mutually profitable corruption deals. The effect of various assumptions about the corruption is then discussed.